Identification of Escherichia Coli in foods prepared in Public Kitchens of Chaclacayo District, Lima, Perú - Zenteno Guerra, Annie Bell (2019)
Objective: The objective of this study was to identify the presence of E. Coli in foods prepared in the kitchensChaclacayo District, Lima. Methods: An experimental study was longitudinal design where the sample consistedof 15 soup kitchens and was non-probability sampling. The instruments used were Petrifilm plates and laboratoryequipment for the collection and analysis of prepared foods. For statistical process worksheet used MicrosoftOffice Excel 2010, using measures of central tendency. Results: From the dining studied, 3 (21.4%) of them hadthe presence of E. Coli. Of the 42 samples tested, in 5 (12%) of which identified the presence of E. Coli, of the5 samples with E. Coli positive 60% were found in stews and 40% in infusions when comparing the presenceof this bacterium in food preparations, as health safety standards for human consumption. Conclusions: It wasconcluded that 79% of the kitchens were considered acceptable and 21% objectionable.